1993
DOI: 10.1099/0022-1317-74-9-1795
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determination of the nucleocapsid protein gene of the porcine epidemic diarrhoea virus confirms that this virus is a coronavirus related to human coronavirus 229E and porcine transmissible gastroenteritis virus

Abstract: The nucleotide sequence of 1.7 kbp cDNA, comprising the region nearest the 3' end of the genome of the porcine epidemic diarrhoea virus (PEDV), has been independently determined for two European isolates of PEDV. Almost identical results were obtained for the two isolates, which were derived from cases of PEDV infection in Belgium and Britain in 1977 and 1987, respectively. The sequences contained a 1323 nucleotide (nt) open reading frame (ORF), which showed moderate identity to the nucleocapsid (N) gene of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 40 publications
1
66
0
Order By: Relevance
“…This confirmed the already observed greater genetic relatedness of PEDV with the TGEV-related subset than with the MHV-related subset and IBV (Bridgen et al, 1993;Duarte et al, 1993a). A multiple alignment of the S protein sequences of PEDV, TGEV, FIPV, CCV and HCV 229E was therefore constructed in order to allow a structural comparison of the molecules (Fig.…”
Section: Inra Unit~ De Virologie Et Immunologiesupporting
confidence: 76%
See 2 more Smart Citations
“…This confirmed the already observed greater genetic relatedness of PEDV with the TGEV-related subset than with the MHV-related subset and IBV (Bridgen et al, 1993;Duarte et al, 1993a). A multiple alignment of the S protein sequences of PEDV, TGEV, FIPV, CCV and HCV 229E was therefore constructed in order to allow a structural comparison of the molecules (Fig.…”
Section: Inra Unit~ De Virologie Et Immunologiesupporting
confidence: 76%
“…The information recently derived from partial sequencing of the viral RNA of two isolates confirmed its previously tentative classification as a member of the Coronaviridae. Four major open reading frames (ORFs) have been identified in the 4 kilobases nearest to the 3' end of the genome (Bridgen et al, 1993;Duarte et al, 1993a). Three of them encode the distinctive coronavirus structural proteins N (nucleocapsid), sM (small membrane) and M (membrane).…”
Section: Inra Unit~ De Virologie Et Immunologiementioning
confidence: 99%
See 1 more Smart Citation
“…Porcine epidemic diarrhea is caused by porcine epidemic diarrhea virus (PEDV), which belongs to the genus Alphacoronavirus within the family Coronaviridae and subfamily Coronavirinae [9]. PEDV is a single-stranded, enveloped, positive-sense RNA virus with an approximately 28-kb genome, including 5 0 and 3 0 untranslated regions (UTR) and seven known open reading frames (ORFs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…The disease was first recognized in Correspondence to: R.F. Li, e-mail: lirenfeng@sina.com England in 1971 (Pensaert et al 1978), and since then, outbreaks have been reported in Europe and Asia (Bridgen et al 1993, Puranaveja et al 2009, Chen et al 2010, and more recently in the United States (Wang et al 2014). In China, although a periodic vaccination strategy has been applied nationwide to control the disease in pig farms, PEDV outbreaks have continued to occur causing large financial losses in the Table 1.…”
Section: Introductionmentioning
confidence: 99%